Dinâmica populacional de Rhipicephalus sanguineus (Latrielle, 1806), em Belo Horizonte, Minas Gerais - Julia Angelica Goncalves da Silveira (2008)
The present study aimed to evaluate the population dynamics of R. sanguineus on dogs living in Belo Horizonte, state of Minas Gerais, Brazil. From August 2006 to July 2007, ticks were collected monthly from 12 adult dogs in nine houses, which were located in the northern and the Venda Nova sanitary districts of the municipal district. Upon collection, questionnaires were applied to owners to obtain data on human parasitism by ixodids and considerations on the management of dogs, which could interfere with the population dynamics of R. sanguineus. All stages of the life cycle of ixodid were found in dogs during every month and were found three peaks in the total population, suggesting that the R. sanguineus holds three generations per year in dogs from Belo Horizonte. The total number of ticks collected was 7,318, of which 5,422 were adults, and the infestation presented three peaks: October, March and July. The total instars immature (larvae and nymphs) found infecting the dogs was 1,896, from this 744 larvae and 1,152 nymphs. Four peaks were observed in the population of larvae (August, November, January and April) and four peaks in the population of nymphs (August, February, April and June). August was the month in which they were collected the largest number of instars and the lowest month of May. Considering the total ixodids collected, the rate of infestation was significantly higher (p<0.05) in winter and in autumn, regarding the spring and summer. The main sites for fixing ticks were: neck, a toracic member, axilla, chest, chest by back to the insertion of the last rib. For the questionnaire it was found that there was no report of parasitism in humans during the trial period. This work was also determined the rate of tick infestation in 2,848 dogs who attended of a pet care department of the small animal veterinary clinic, located in the sanitary district of Venda Nova. It was found that 7.8% of the dogs were infested with ticks and the infestation was higher in the winter and autumn (p<0.05) than in the spring and the summer. The percentage of male dogs infested with ticks was significantly higher (58.29%) than the percentage of infested female dogs (41.70%)